Rahmat Panggilan Misioner dalam Sakramen Penguatan:: Berdasarkan Penerima Sakramen di Paroki Mariae Beatae Virginis Katedral Bogor - Tirtowijoyo, Gerald Prayugo (Parahyangan Catholic University, 2025)
This study aims to explore and analyse the grace of the missionary calling within the Sacrament of Confirmation, focusing on the lived experiences of Confirmation recipients at the Parish of Beatae Mariae Virginis (BMV) Cathedral in Bogor, West Java. Employing a qualitative approach, the research involved in-depth interviews and questionnaires distributed to parishioners who had received the Sacrament of Confirmation, particularly among adolescents and adults. The findings reveal that the Sacrament of Confirmation is perceived not merely as a significant milestone in one’s Catholic faith journey, but also as a powerful impetus for active participation in missionary and ecclesial service. Recipients of the sacrament recognise their responsibility to bear witness to Christ through the guidance and empowerment of the Holy Spirit. This study affirms that the Sacrament of Confirmation holds profound relevance in fostering and strengthening the missionary spirit among Catholics, especially adolescent and adult recipients in the BMV Cathedral Parish of Bogor. The practical implications of these findings are expected to assist the Church in designing more effective accompaniment and formation programmes to nurture and sustain the missionary vocation of those who have received the Sacrament of Confirmation.